A model of the home food environment pertaining to childhood obesity - Rosenkranz, Richard R.; Dzewaltowski, David A. (My University, 2008)
The home food environment can be conceptualized as overlapping interactive domains composed of built and natural, sociocultural, political and economic, micro-level and macro-level environments. Each type and level of environment uniquely contributes influence through a mosaic of determinants depicting the home food environment as a major setting for shaping child dietary behavior and the development of obesity. Obesity is a multifactorial problem, and the home food environmental aspects described here represent a substantial part of the full environmental context in which a child grows, develops, eats, and behaves. The present review includes selected literature relevant to the home food environment's influence on obesity with the aim of presenting an ecologically informed model for future research and intervention in the home food environment.
Keywords: Children; Obesity; Home food environment; Obesigenic; Obesogenic